MR Angiography of Peripheral Arterial Stents: In Vitro Evaluation of 22 Different Stent Types - Matthias C. Burg; Alexander C. Bunck; Harald Seifarth; Boris Buerke; Harald Kugel; Volker Hesselmann; Michael Köhler; Walter Heindel; David Maintz (Radiology Research and Practice)
Purpose. To evaluate stent lumen visibility of a large sample of different peripheral arterial (iliac, renal, carotid) stents using magnetic resonance angiography in vitro. Materials and Methods. 21 different stents and one stentgraft (10 nitinol, 7 316L, 2 tantalum, 1 cobalt superalloy, 1 PET + cobalt superalloy, and 1 platinum alloy) were examined in a vessel phantom (vessel diameters ranging from 5 to 13 mm) filled with a solution of Gd-DTPA. Stents were imaged at 1.5 Tesla using a T1-weighted 3D spoiled gradient-echo sequence. Image analysis was performed measuring three categories: Signal intensity in the stent lumen, lumen visibility of the stented lumen, and homogeneity of the stented lumen. The results were classified using a 3-point scale (good, intermediate, and poor results). Results. 7 stents showed good MR lumen visibility (4x nitinol, 2x tantalum, and 1x cobalt superalloy). 9 stents showed intermediate results (5x nitinol, 2x 316L, 1x PET + cobalt superalloy, and 1x platinum alloy) and 6 stents showed poor results (1x nitinol, and 5x 316L). Conclusion. Stent lumen visibility varies depending on the stent material and type. Some products show good lumen visibility which may allow the detection of stenoses inside the lumen, while other products cause artifacts which prevent reliable evaluation of the stent lumen with this technique.